Serum KL-6 as a novel disease marker in adolescent and adult Cystic Fibrosis - Ohshimo, S.; Bonella, F.; Grammann, et al., N. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Background: Cystic fibrosis (CF) is a chronic progressive disease leading to obstructive pulmonary impairment, fibrosis and shortened life expectancy. Serum levels of KL-6, high molecular weight human MUC1 mucin, are increased in the majority of patients with various interstitial lung disorders.Whether they are also elevated in CF has not been investigated before. Objective: To evaluate whether serum KL-6 levels are elevated and correlate with pulmonary function variables in CF. Design: Serum KL-6, lactate dehydrogenase (LDH) and C-reactive protein (CRP) levels were measured in 72 consecutive CF and 80 age- and sex-matched healthy control subjects. The relationship between serum KL-6 levels and pulmonary function variables was analyzed. Results: Serum KL-6 levels in CF patients were significantly increased compared to healthy subjects. Receiver operating characteristic curve analysis revealed that the diagnostic accuracy of KL-6 was better than that of LDH and CRP. Serum KL-6 levels showed an inverse relationship with vital capacity (VC) % predicted and forced expiratory volume in one second (FEV1) % predicted. Conclusions: Serum KL-6 levels are elevated and appear to be correlated with pulmonary function variables in CF. These results suggest that KL-6 may be a useful noninvasive marker to monitor disease severity.